In the shadow of the Lammermuirs: archaeological investigations of prehistoric and early medieval sites between Thorntonloch and Boonslie, East Lothian for the Onshore Cable Route for the Neart na Gaoithe Offshore Wind Farm - Saunders, Ben; López-Dóriga, Inés; Treasure, Ed; Seager Smith, Rachael; Shaffrey, Ruth; Swales, Christopher; Valdez-Tullett, Andrew (Proceedings of the Society of Antiquaries of Scotland, 2024)
Wessex Archaeology completed archaeological investigations on the Onshore Transmission Works for the Neart na Gaoithe Offshore Wind Farm between 2015 and 2021. These included geophysical survey, evaluation trenching, targeted strip, map and sample excavations, and watching briefs on the cable route and associated infrastructure between the landfall at Thorntonloch and the grid connection at Crystal Rig II Wind Farm, both in East Lothian. The investigations found that few archaeological features were present within the section of the cable route within the coastal plain between Thorntonloch and Innerwick, and within the upland area approaching Crystal Rig (excluding the medieval township of Boonslie). Features relating to a wide range of periods, dominated by the prehistoric, were found within the transitional zone to the south-west of Innerwick between the Lammermuir foothills and the coastal plain. These included an Early Neolithic pit cluster and possible trackway, pits dated to the Late Neolithic and Early Bronze Age, and a Late Bronze Age/Early Iron Age pit alignment. Within the immediate area of the pit alignment there was also evidence for later Iron Age and early medieval occupation. The cable route was designed to avoid the extant remains of Boonslie, an upland medieval township around the headwaters of the Boonslie Burn, but some previously undetected earthworks were uncovered and investigated, as well as the earliest dated feature found in the works: a pit containing burnt material dating to the Mesolithic. The excavations also uncovered evidence for the deliberate landscaping of agricultural fields during the post-medieval and modern period to give a greater area of cultivatable terrain.